High‐Density Lewis Acid Sites in Porous Single‐Crystalline Monoliths to Enhance Propane Dehydrogenation at Reduced Temperatures. (10th March 2021) - Lin, Guoming; Su, Yunqi; Duan, Xiuyun; Xie, Kui
Abstract: The non‐oxidative dehydrogenation of propane to propylene plays an important role in the light‐olefin chemical industry. However, the conversion and selectivity remain a fundamental challenge at low temperatures. Here we create and engineer high‐density Lewis acid sites at well‐defined surfaces in porous single‐crystalline Mo2 N and MoN monoliths to enhance the non‐oxidative dehydrogenation of propane to propylene. The top‐layer Mo ions with unsaturated Mo‐N1/6 and Mo‐N1/3 coordination structures provide high‐density Lewis acid sites at the surface, leading to the effective activation of C−H bonds without the overcracking of C−C bonds during the non‐oxidative dehydrogenation of propane. We demonstrate a propane conversion of ≈11 % and a propylene selectivity of ≈95 % with porous single‐crystalline Mo2 N and MoN monoliths at 500 °C. Abstract : Porous single‐crystalline molybdenum nitride monoliths can be grown with a high density of Lewis acid sites at the well‐defined surface. This porous material shows enhanced non‐oxidative dehydrogenation of propane at reduced temperatures.